2019
DOI: 10.1108/hff-04-2019-0343
|View full text |Cite
|
Sign up to set email alerts
|

Two-step numerical simulation of the heat transfer from a flat plate to a swirling jet flow from a rotating pipe

Abstract: Purpose Impinging jets have been widely studied, and the addition of swirl has been found to be beneficial to heat transfer. As there is no literature on Reynolds-averaged Navier Stokes equations (RANS) nor experimental data of swirling jet flows generated by a rotating pipe, the purpose of this study is to fill such gap by providing results on the performance of this type of design. Design/methodology/approach As the flow has a different behaviour at different parts of the design, the same turbulent model can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(44 citation statements)
references
References 83 publications
1
43
0
Order By: Relevance
“…The reason is attributed to two important facts. First, as stated in Granados-Ortiz et al (2019), this imbalance between experimental-computational works is also observed in classic literature on heat transfer by impinging air or water jets. It was discussed earlier in this section that the modeling of turbulence in impinging jets is challenging (it is considered a case of complex flow because of the sudden changes in velocity magnitude and direction, the shear-layer interaction and the transition to turbulence (Granados-Ortiz & Ortega-Casanova, 2020)).…”
Section: Use Of Nanofluids In Heat Transfer With Impinging Jetsmentioning
confidence: 81%
See 3 more Smart Citations
“…The reason is attributed to two important facts. First, as stated in Granados-Ortiz et al (2019), this imbalance between experimental-computational works is also observed in classic literature on heat transfer by impinging air or water jets. It was discussed earlier in this section that the modeling of turbulence in impinging jets is challenging (it is considered a case of complex flow because of the sudden changes in velocity magnitude and direction, the shear-layer interaction and the transition to turbulence (Granados-Ortiz & Ortega-Casanova, 2020)).…”
Section: Use Of Nanofluids In Heat Transfer With Impinging Jetsmentioning
confidence: 81%
“…The impinging jet considered in the present paper is turbulent. The existence of turbulence in wall jets is, in fact, recommendable since the radial Nusselt distribution strongly depends on this feature, as shown by several authors (Behnia et al, 1999;Granados-Ortiz et al, 2019;Uddin et al, 2013). These authors explicitly outlined the presence of secondary peaks in the Nusselt profile due to the transition to turbulent flow.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In some cases, the grooves were cut on the inner side of jet with different twisting angles to rotate the outlet flow of fluid. The effects of swirling jets on the flow and heat transfer of fluid were investigated by many authors [20][21][22]. The study of previous works on the effects of swirling jet on the flow and heat transfer of fluid led the authors to propose the idea of using swirling exhaust plume to disperse the pollutant.…”
Section: Introductionmentioning
confidence: 99%